E-029 Progressively soft coils for treatment of intracerebral aneurysms – an initial experience with the smart coil at two centers. (23rd July 2017) - Spiotta,; Fargen, K; Lena, J; Chaudry, I; Turner, R; Turk, A; Huddle, D; David, L; Bellon, R; Frei, D
Abstract : Introduction: Endovascular therapy for cerebral aneurysms has increasingly been adopted as a viable treatment strategy for its minimally invasive but effective approach. This rising adoption has been correlated with an evolution in coil technology, including the recently FDA-cleared SMART Coil. In contrast to traditional bare metal coils, which have historically been designed with a uniform degree of softness, SMART Coils are designed with transitional softness, allowing the coil to become progressively softer as it is deployed. This mitigates catheter kickback while enabling the coil to pack more tightly and achieve greater packing density. Herein, we present our initial technical experience on aneurysm obliteration with SMART Coils. Methods: Following IRB approval, a retrospective review was conducted at 2 centers to identify consecutive patients presenting with cerebral aneurysms wherein at least 1 SMART Coil was employed as intervention. Patient characteristics, procedural metrics, angiographic outcome, and procedural outcome data were captured to evaluate the safety and efficacy of the use of SMART Coils. Adverse events were classified as major or minor, depending upon whether additional intervention was needed (major). Occlusion outcome was graded using the Raymond Roy Occlusion Classification, in which Class I was complete obliteration, and Class III denotes residual aneurysm. Results: Between July 2015 and January 2016, 59 patients were identified wherein embolization was performed with at least 1 SMART Coil; 44% presented with ruptured aneurysms. The mean aneurysm size was 5.9±2×4.5±2 mm, with an average neck diameter of 3.4±1 mm. In total, 54.2% of patients were treated exclusively with SMART Coils while the remainder used various framing or finishing coils. Balloon-assisted coiling was employed in 33.9%, and stent-assisted coiling in 47.5% of all cases. More specifically, in patients wherein SMART Coils were used exclusively, 34.4% were treated with balloon assistance, and 43.4% employed stent-assisted coiling. In the remaining patients, these rates were 77.8% and 51.9%, respectively, for balloon and stent-assisted coiling. Minor adverse events occurred in 10.1%, and included thrombus formation along the coil mass (n=4), thrombus formation within the stent (n=2), and coil prolapse (n=2); none resulted in sequelae. No major adverse events observed. On average, 6.4 ±4 coils were deployed per aneurysm, with a mean fluoroscopy time of 48.5±22 min. Occlusion outcomes included Class I in 33.9%, Class II in 37.3% and Class III in 28.8%. No rebleeds have been observed. Conclusion: The progressive design of SMART Coils offered appreciable clinical advantages during deployment. In addition, SMART demonstrated satisfactory safety and efficacy outcomes in treatment of a wide variety aneurysms, both ruptured and unruptured. Disclosures: A. Spiotta: 1; C; Penumbra, Inc.. 2; C; Penumbra, Inc. 4; C; Penumbra, Inc. K. Fargen: None. J. Lena: 2; C; Penumbra, Inc. I. Chaudry: 1; C; Penumbra, Inc. 4; C; Penumbra, Inc. R. Turner: 1; C; Penumbra, Inc. 4; C; Penumbra, Inc. A. Turk: 1; C; Penumbra, Inc. 4; C; Penumbra, Inc.. D. Huddle: None. L. David: None. R. Bellon: None. D. Frei: 2; C; Penumbra, Inc., Codman, Microvention, Stryker, Siemens, Codman, Microvention, Stryker, Siemens. 4; C; Penumbra, Inc.